America—Still in the Hero's Grip. (2nd January 2018) - Stadelmann Wright, Anja
Abstract : Although the United States is clearly still reeling from its current and recent exported wars, it has never gotten close enough to fully witness their actual horror. As a result, the nation's profound identification with the archetypes of the warrior and hero has never undergone a corrective experience. The country's one-sided myth of its own exceptionalism and goodness has created not only an unattainable image to live up to, but also its flip side—a very repressed and ignored shadow, which is liable to pop up in highly unregulated forms. The psychic split this creates is now being played out in a deeply divided nation and the seemingly sudden emergence of a president who carries all the shadow aspects of the hero archetype. The United States is certainly not the only nation with a narrative elevating itself above all others—or that has ended up enthroning its own shadow. But because of its size and power, the consequences are much more damaging. It would serve the United States well to relativize its view of itself, and for it to take a more appropriate place among the nations of this world. However, history shows that this kind of shift does not happen voluntarily; instead it is forced upon a country by its own failure. It remains to be seen if the United States will be able to make the necessary leap in consciousness to avoid following in history's footsteps.